Pre-Islamic ’Ḥamāsah’ verses from north-eastern Jordan: a new Safaitic poetic text from Marabb al-Shurafāʾ, with further remarks on the ʿĒn ʿAvdat inscription and KRS 2453 - Al-Jallad, Ahmad (Proceedings of the Seminar for Arabian Studies, 2017)
This contribution presents a decipherment of a new Safaitic inscription argued to contain a short war poem. This is followed by a discussion of its relationship with the other two Old Arabic poetic texts known to date, KRS 2453 and the ʿĒn ʿAvdat inscription. The article concludes with some further notes on KRS 2453.